Study of the compressive strength and unit weight of specimens made from lahar sand and lahar sand derived materials - Celzo, Ma. Salvacion I. (1999)
Continuous work on lahar had been undertaken by different research groups in order to utilize the materials that had been considered a disaster to our country. This study primarily aims to contribute to the studies that were already done by introducing the method of separation in the lahar sand in order to produce new materials with the purpose application in the construction industry.
Lahar concentrates and lahar tailings were the materials derived from lahar. The 50-mm cube specimens that were produced using the derived materials were of good quality either in terms of the compressive strength of specimens made of lahar tailings were considerably lighter than the specimens made of the other sand samples. Combination of the strength and the unit weight of the samples gave a possibility in the application of lightweight load bearing concrete hollow blocks. Another aspect that was investigated in the study is the substitution of lahar sand derived products in place of perlite. The study showed a positive result indicated by high strength attained by the specimens made of the lahar sand derived materials.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Lahars -- Philippines -- Zambales; Aggregates (Building materials) -- Philippines; Concrete blocks; Perlite